2018
DOI: 10.9770/jesi.2018.6.1(26)
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial assessment of sustainable development technologies for power energy sector

Abstract: This paper provides a comparative entrepreneurial analysis of modern combined-cycle power generation technologies and future-oriented high-efficiency oxy-fuel combustion cycles with zero emissions. Considering the main criteria for sustainable development, we identify the generation technology that provides the lowest cost of electricity supply and the maximum economic efficiency of investments with equally high environmental indicators. Based on a comprehensive literature review and comparison of the technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…an emphasis on the public choice of "green" technologies, simplification and optimization of this choice; -reframing benefits; -changing the time structure of costs and benefits; -emphasis on the symbolic attributes of new technologies [18]; -behavior change aimed to reduce energy consumption in households [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…an emphasis on the public choice of "green" technologies, simplification and optimization of this choice; -reframing benefits; -changing the time structure of costs and benefits; -emphasis on the symbolic attributes of new technologies [18]; -behavior change aimed to reduce energy consumption in households [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hydroelectric power plants are facilities that have many other functions besides generating electricity (Sachdev, Akella, & Kumar, 2015;Singh & Singal, 2017). They affect the stabilization of (Blazejczak, Braun, Edler, & Schill, 2014;Dudin, Frolova, Protopopova, Mamedov, & Odintsov, 2019;Lavrinenko, Ignatjeva, Ohotina, Rybalkin, & Lazdans, 2019;Lisin, Kurdiukova, & Ketoeva, 2018;Rogalev, Komarov, Kindra, & Zlyvk, 2018;Tolstolesova, Yumanova, Mazikova, Glukhikh, & Vorobieva, 2019).…”
Section: Sustainable Development Of Hydropowermentioning
confidence: 99%
“…Renewable energy sources including hydroenergy provide economic growth and climate change mitigation (Bilan et al, 2019; Lyeonov, Pimonenko, Bilan, Štreimikienė, & Mentel, 2019; Simionescu, Bilan, Krajňáková, Streimikiene, & Gędek, 2019; Vasylieva, Lyulyov, Bilan, & Streimikiene, 2019) and have positive impact on innovation, entrepreneurship and competitiveness of the regions (Blazejczak, Braun, Edler, & Schill, 2014; Dudin, Frolova, Protopopova, Mamedov, & Odintsov, 2019; Lavrinenko, Ignatjeva, Ohotina, Rybalkin, & Lazdans, 2019; Lisin, Kurdiukova, & Ketoeva, 2018; Rogalev, Komarov, Kindra, & Zlyvk, 2018; Tolstolesova, Yumanova, Mazikova, Glukhikh, & Vorobieva, 2019).…”
Section: Sustainable Development Of Hydropowermentioning
confidence: 99%
“…There is also the opinion that, rather than displaying a negative impact on economic growth, environmental policy could lead to competitiveness, as "restrictive environmental policies had a growth-promoting effect, in particular, on productivity growth via their influence on ICT capital accumulation" (De Santis & Lasinio, 2015, p. 19;Yang, Tseng, & Chen, 2012;Wu & Wang, 2008;Yörük & Zaim, 2005), inspiring new power generation technologies with zero emissions (Rogalev, Komarov, Kindra, & Zlyvko, 2018). This "win-win" approach, otherwise criticized for its excessive theoretical approach and the free-lunch argument, is mainly associated with the contributions of Michael Porter (1998), or Porter and van der Linde (1995), who have suggested that "well-designed environmental policies might actually enhance productivity and increase innovation, yielding direct economic benefits next to the environmental benefits" (Koźluk & Zipperer, 2015, p. 156).…”
Section: Theoretical Backgroundmentioning
confidence: 99%